Breast-conserving surgery without axillary surgery and radiation versus mastectomy plus axillary dissection in elderly breast cancer patients: A retrospective study - Zhong, Ying; Wang, Zhe; Xu, Yali; Zhou, Yidong; Mao, Feng; Shen, Songjie; Sun, Qiang (Frontiers in Oncology, 2023)
Background: The high relative mortality rate in elderly breast cancer patients is most likely the result of comorbidities rather than the tumor load. Foregoing axillary lymph node dissection or omitting radiotherapy after breast-conserving surgery (BCS) does not affect the prognosis of elderly breast cancer patients. We sought to assess the safety of breast-conserving surgery without axillary lymph node dissection as well as breast and axillary radiotherapy (BCSNR) in elderly patients with early-stage breast cancer. Methods: We retrospectively included 541 consecutive breast cancer patients aged over 70 years with clinically negative axillary lymph nodes in one clinical center. Of these patients, 181 underwent mastectomy plus axillary lymph node dissection (MALND) with negative axillary cleaning and 360 underwent BCSNR. Results: After a median follow-up of 5 years, there was no significant difference between the BCSNR and MALND groups in either distant recurrence-free survival (DRFS) (p=0.990) or breast cancer-specific survival (p=0.076). Ipsilateral axillary disease was found in 11 (3.1%) patients in the BCSNR group and 3 (1.7%) patients in the MALND group; this difference was not significant (p=0.334). We did not observe a significant difference in distant recurrence between the groups (p=0.574), with 25 (6.9%) patients in the BCSNR group experiencing distant recurrence compared to 15 (8.3%) patients in the MALND group. Our findings did show a significant difference in ipsilateral breast cancer recurrence (IBTR), with 31 (8.6%) patients in the BCSNR group experiencing IBTR compared to only 2 (1.1%) patients in the MALND group (p=0.003). Conclusion: BCSNR is a safe treatment option for elderly breast cancer patients with clinically negative axillary lymph nodes.